The structure and modified properties of a self-dimerised Cu(ii) inclusion complex in γ-cyclodextrins. Issue 14 (15th March 2023) - Hamaguchi, Tomohiko; Ishikawa, Ryuta; Mishima, Akio; Hayami, Shinya; Ohba, Masaaki; Satoh, Minoru; Kawata, Satoshi
Abstract : Cu fragments in γ-cyclodextrins show different properties from those of unincluded fragments caused by the confinement and the interaction between Cu fragments. Abstract : Inclusion structures incorporating more than one guest molecule are elusive because confinement alters their molecular properties. We report the solid-state characterization of an inclusion complex comprising two γ-cyclodextrins and two [Cu(2-pyridinemethanolate)(2-pyridinemethanol)]PF6 units. Quantum calculation reveals that interfragment charge transfer occurs. The confined Cu fragment and the unincluded "linear chain [Cu(2-pyridinemethanolate)(2-pyridinemethanol)]PF6 " exhibit different properties.